Yield and nutrition of sunflower fertilized with sewage sludge - Hermann C. de Albuquerque (Revista Brasileira de Engenharia Agrícola e Ambiental - Agriambi, 2015)
ABSTRACT The aim of this study was to evaluate the effect of thermally dried sewage sludge on soil fertility, growth and yield of sunflower. The experiment was conducted in a Nitosol area of the Institute of Agricultural Sciences of the Federal University of Minas Gerais, in Montes Claros-MG, Brazil. The treatments consisted of four doses of sewage sludge (0, 10, 20 or 30 t ha-1, dry weight basis), with six replicates in a randomized block design. The levels of nutrients in soil and plant, soil fertility indices, stem diameter, plant height, head diameter and grain yield were evaluated. Stem diameter, plant height, head diameter and grain yield increased with increasing doses of sewage sludge. The application of the residue increased linearly the contents of soil organic matter and N in sunflower leaves. On the other hand, pH, the exchangeable bases, total and effective cation exchange capacity, base saturation, H+Al, Al, soil contents of P, K, Ca, Mg, S, Zn, Cu, Mn, Fe and B, and the leaf contents of P, K, Ca, Mg, S, Zn, Cu, Mn, Fe and B were not influenced by the application of sewage sludge doses of up to 30 t ha-1.